2003
DOI: 10.1124/dmd.31.5.606
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nonspecific Binding to Microsomes and Phospholipid on the Inhibition of Cytochrome P4502D6: Implications for Relating in Vitro Inhibition Data to in Vivo Drug Interactions

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:The effects of microsomal concentration on the inhibitory potencies of four compounds-fluoxetine, quinidine, imipramine, and ezlopitant-on heterologously expressed recombinant CYP2D6-catalyzed bufuralol 1-hydroxylase activity were determined. Increasing microsomal concentration from 0.0088 to 2.0 mg/ml, using additional microsomes not containing cytochrome P450, resulted in a marked increase in IC 50 and K I values for fluoxetine, ezlopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 14 publications
3
77
0
Order By: Relevance
“…Overprediction of drug-drug interactions has been reported for CYP3A4 inactivation by various kinase inhibitors (Kenny et al, 2012). For experimentally determined kinetic parameters (such as K i ), nonspecific binding and albumin tend to decrease "effective concentrations" of some drugs and lead to overestimation of parameters obtained from HLM incubations (Margolis and Obach 2003;Wattanachai et al, 2011;Nagar and Korzekwa 2012). The decreased inhibitory potency due to overestimation of K i values may result in underprediction of drug-drug interaction potential, a phenomenon was not seen during our analysis.…”
Section: Discussionmentioning
confidence: 51%
“…Overprediction of drug-drug interactions has been reported for CYP3A4 inactivation by various kinase inhibitors (Kenny et al, 2012). For experimentally determined kinetic parameters (such as K i ), nonspecific binding and albumin tend to decrease "effective concentrations" of some drugs and lead to overestimation of parameters obtained from HLM incubations (Margolis and Obach 2003;Wattanachai et al, 2011;Nagar and Korzekwa 2012). The decreased inhibitory potency due to overestimation of K i values may result in underprediction of drug-drug interaction potential, a phenomenon was not seen during our analysis.…”
Section: Discussionmentioning
confidence: 51%
“…The k inact and K I values for racemic fluoxetine agree well with the k inact and apparent K I values of 0.03 minϪ1 and 8 M reported by McGinnity et al (2006), respectively. Values were not corrected for nonspecific binding, which can be substantial for fluoxetine (Margolis and Obach, 2003). Correcting for unbound fluoxetine, the estimates of K I values would be [10-fold lower (McGinnity et al, 2006)] and are within steady-state total plasma levels of fluoxetine (ranging from 0.15 to 1.5 M) found after therapeutic dosing of fluoxetine (Orsulak et al, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…14) After a 5-min incubation at 37°C, the mixture was centrifuged at 105000 g for 60 min at 4°C, 13) and the concentration of nilvadipine in the supernatant was measured by HPLC with an analytical column Inertsil ODS-3 (150ϫ4.6 mm I.D., GL Sciences Inc., Tokyo, Japan). The column temperature was set at 40°C.…”
Section: Determination Of Free Fraction In Incubation Mixturementioning
confidence: 99%
“…Recent studies have been shown that inhibition constants (K i ) for drugs as inhibitors of microsomal drug-metabolizing enzymes, such as CYP, should be correlated for the extent of nonspecific binding to components of the in vitro matrix, by measurement of the unbound fraction under the incubation condition, to yield more accurate determination of the constant. 13) However, there are few such detailed studies on the effect of nilvadipine on human hepatic CYP-mediated drugmetabolizing activity.…”
mentioning
confidence: 99%